Effect of protic ionic liquid nanostructure on phospholipid vesicle formation. Issue 7 (23rd January 2017) - Bryant, Saffron J.; Wood, Kathleen; Atkin, Rob; Warr, Gregory G.
Abstract : The formation of lyotropic liquid crystals and vesicles by phospholipids in protic ionic liquids has been found to depend strongly on the amphiphilic nanostructure of the solvent using polarizing optical microscopy, differential scanning calorimetry, and small angle X-ray and neutron scattering. Abstract : The formation of bilayer-based lyotropic liquid crystals and vesicle dispersions by phospholipids in a range of protic ionic liquids has been investigated by polarizing optical microscopy using isothermal penetration scans, differential scanning calorimetry, and small angle X-ray and neutron scattering. The stability and structure of both lamellar phases and vesicle dispersions is found to depend primarily on the underlying amphiphilic nanostructure of the ionic liquid itself. This finding has significant implications for the use of ionic liquids in soft and biological materials and for biopreservation, and demonstrates how vesicle structure and properties can be controlled through selection of cation and anion. For a given ionic liquid, systematic trends in bilayer thickness, chain-melting temperature and enthalpy increase with phospholipid acyl chain length, paralleling behaviour in aqueous systems.